Emerging Challenges in Rural Non-Farm Sector and Inequality in Rural India: Insight from IHDS Survey - Devi, Bisla; Ranganathan, Thiagu (Finance & Economics Review, 2021)
Purpose: This paper highlights the changing patterns of income diversification and the effects of various socio-economic factors influencing the non-farm (NF) income of rural households in India. The study also explores the inequality effects of the non-farm earnings of the households by using the Fields inequality decomposition. Method: The study compares and evaluates the determinants and trends of inequality in 2004-2005 and 2011-2012 in the NF sector. It uses nationally representative data from two rounds of the Indian Human Development Survey (IHDS), which includes a panel of 36,278 households at all levels in India. The Censored Least Absolute Deviation (CLAD) model is used to estimate household determinants for non-farm income. The Fields decomposition decomposes total income inequality by considering the socio-economic factors. Results: The study finds that variations in non-farm earnings have increased. Field's Income Inequality Decomposition estimates show that income inequalities between households are significantly high due to factors such as education, level of the household head, land ownership, and population density, but also appear to be declining in 2011-12. Also, the earning gaps based on gender, age, and geographical zones have increased. Implications: Overall, the non-farm income during the studied period was observed to be biased towards the better-off households. However, it opened up opportunities for underprivileged households as well. The non-farm sector has huge potential in augmenting incomes for unprivileged rural households. Therefore, the government should pay attention to this sector as a means of reducing income inequality and alleviating poverty.